Betrachtungen zu Harariner grammatischen Termini - Wagner, Ewald (Aethiopica, 2014)
In 1986, Abdurahmān Maḥamad Qorām published a Harari Grammar which made him the first Harari to describe his mother tongue in the language, itself. For this purpose he had to invent a grammatical terminology in Harari. 26 years later, Ali Naji, also a native speaker, used in his book on Harari grammar almost the same terms. That shows that Qorām’s terminology has won acceptance in the meantime. The present article investigates the means which Qorām applied to create the new terminology. Rarely he took over the terms of foreign languages unchanged. More often he translated Arabic, English and Amharic terms. In most cases, however, he formed new expressions, exploiting the inherent lingusitic possibilities of the Harari language.